Oxidative stress and neuroprotective effect of metabolites of Blackberry digestion using a neurodegeneration cell model - Figueira, Inês Margarida Lourenço (2012)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2011